Polysomnographic Features of Sleep Disturbances and REM Sleep Behavior Disorder in the Unilateral 6-OHDA Lesioned Hemiparkinsonian Rat - Quynh Vo; Timothy P. Gilmour; Kala Venkiteswaran; Jidong Fang; Thyagarajan Subramanian (Parkinson's Disease)
Sleep pattern disruption, specifically REM sleep behavior disorder (RBD), is a major nonmotor cause of disability in PD. Understanding the pathophysiology of these sleep pattern disturbances is critical to find effective treatments. 24-hour polysomnography (PSG), the gold standard for sleep studies, has never been used to test sleep dysfunction in the standard 6-OHDA lesioned hemiparkinsonian (HP) rat PD model. In this study, we recorded 24-hour PSG from normal and HP rats. Recordings were scored into wake, rapid eye movement (REM), and non-REM (NREM). We then examined EEG to identify REM periods and EMG to check muscle activity during REM. Normal rats showed higher wakefulness (70–80%) during the dark phase and lower wakefulness (20%) during the light phase. HP rats showed 30–50% sleep in both phases, less modulation and synchronization to the light schedule (P<0.0001), and more long run lengths of wakefulness (P<0.05). HP rats also had more REM epochs with muscle activity than control rats (P<0.05). Our findings that the sleep architecture in the HP rat resembles that of PD patients demonstrate the value of this model in studying the pathophysiological basis of PD sleep disturbances and preclinical therapeutics for PD related sleep disorders including RBD.